Popular Skin-of-Color Dermatology Social Media Hashtags on TikTok From 2021 to 2022: Content Analysis - Jeemin Kang; Mindy D Szeto; Lois Suh; Jadesola T Olayinka; Robert P Dellavalle (JMIR Publications, 2024)
AbstractTikTok is a social media platform that can educate users about dermatology, but this longitudinal analysis of skin of color-related TikTok hashtags from 2021 to 2022 suggests that nondermatologist influencers continue to dominate content creation, highlighting the need for more participation from board-certified dermatologists to actively counter misinformation and address potential disparities in skin-of-color health care.